Comparative Effectiveness of a Commercial Mouthwash and an Herbal Infusion in Oral Health Care - Gabriela Ciavoi; Luciana Dobjanschi; Tunde Jurca; Gyongyi Osser; Ioana Scrobota; Annamaria Pallag; Mariana Eugenia Muresan; Laura Gratiela Vicaș; Eleonora Marian; Farah Bechir; Laurenta Lelia Mihai; Enikő Béres; et al. (Applied Sciences, 2021)
Mouthrinse solutions represent a group of products used for maintaining oral hygiene after tooth brushing. Substances contained by plants bring benefits for the whole mouth health. The purpose of this study was to comparatively evaluate the effectiveness of a commercial mouthwash and of an herbal infusion on dental plaque formation and gingival inflammation. The participants in the study (90 patients) were divided into two groups, the CM group, which rinsed with a commercial fluoride-containing mouthwash and the IM group, which used an herbal infusion. The Silness–Loe plaque index (PI) and the Loe–Silness gingival index (GI) were assessed at baseline and in three following monitoring sessions. Both mouthwashes used had good results in reducing plaque index and gingival index values. In all monitoring sessions, the average PI value calculated in the CM group was relatively lower than in the IM group, probably because of the fluoride contained in the commercial mouthwash. The average GI value calculated in the CM group was slightly higher in showing gingival inflammation than that of the IM group, therefore the IM group had a better average result than the CM group in GI value. Herbal mouthwashes are adequate to induce proper oral prevention through the preservation of good oral health.